Analisis Hubungan Gambaran Diri terhadap Kualitas Hidup Penderita Kusta - Toru, Veronika (Poltekkes Kemenkes Kupang, 2022)
Introductions: Data from the Nggaha Ori Angu health center in 2015 there were PB (Pausi Basiler) 5 people, while MB (Multi Basiler) 4 people, in 2016 patients with PB 6 people while MB 5 people in 2017 with PB 7 people, MB 5 people. Leprosy if handled carefully can cause several problems for people with leprosy such as problems faced, especially in the eyes, hands and feet (2012). The aim this tudy to analyze the self-concept of the quality of life of people with leprosy in the working area of the Nggoa Health Center, East Sumba Regency. Methods: This study used an analytic study with a cross sectional design. Held in July 2019 in the Nggoa Health Center Work Area, East Sumba Regency. The sample size is 34 people with total sampling technique. Result: The average self-concept andquality of life of leprosy patients is not good. There is a relationship between self-image (p 0.022), and the quality of life of people with leprosy at the Nggoa Health Center, East Sumba Regency. Conclusion: That most people with leprosy have a poor self-image, and self-image with the quality of life of leprosy patients is very closely related. To the family as the most important person to provide more intensive support, and the health center to be actively involved in services for leprosy patients to provide promotive and curative actions for leprosy sufferers. keywords: Leprosy patients; quality of life; self image